2011
DOI: 10.1016/j.dsr.2011.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Diet of mid-Atlantic Sowerby's beaked whales Mesoplondon bidens

Abstract: This article appeared in a journal published by Elsevier. The attached copy is furnished to the author for internal non-commercial research and education use, including for instruction at the authors institution and sharing with colleagues.Other uses, including reproduction and distribution, or selling or licensing copies, or posting to personal, institutional or third party websites are prohibited. a b s t r a c tThe first mid-Atlantic diet of Mesoplodon beaked whales is presented, from ten Sowerby's Mesoplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 28 publications
3
23
0
Order By: Relevance
“…Our fi ndings are similar to those of Pereira et al (2011), who examined the stomach contents of 10 stranded Sowerby's beaked whales from the Azores and found a predominance of small fi sh prey. It is important to note that all but one of the whales that we examined were killed at sea, and, with the exception of the single stranded animal, they were apparently healthy at the time of their death.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Our fi ndings are similar to those of Pereira et al (2011), who examined the stomach contents of 10 stranded Sowerby's beaked whales from the Azores and found a predominance of small fi sh prey. It is important to note that all but one of the whales that we examined were killed at sea, and, with the exception of the single stranded animal, they were apparently healthy at the time of their death.…”
Section: Discussionsupporting
confidence: 88%
“…The presence of intact prey in the esophagus of one specimen and the large numbers of prey items in the stomachs that we examined indicate that these animals had been foraging before death. The average minimum number of prey in the stomachs that we examined was more than 600 (4789 fi shes, plus 73 squids, in all 8 stomachs combined), compared with 85 prey in the stranded specimens examined by Pereira et al (2011). We believe the stomach contents of the whales that we examined are representative of the summer diet of Sowerby's beaked whales along the continental shelf break off the northeastern coast of the United States.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…However, recent research has shown that beaked whales may show dietary plasticity (MacLeod et al, 2003). In the Azores, the diet of Sowerby's beaked whale (Mesoplodon bidens) is composed essentially of meso-and bathypelagic fish, with little contribution from cephalopods (Pereira et al, 2011). Night-time sea surface temperature was retained in the models of all species in this group and, apart from the sperm whale, was highly influential in the models consistent with a seasonal presence of beaked whales in the region ( Table 3).…”
Section: Sperm and Beaked Whalesmentioning
confidence: 99%